From Stem Cells to Bone-Forming Cells - Donsante, Samantha (Int J Mol Sci, 2021)
Bone formation starts near the end of the embryonic stage of development and continues throughout life during bone modeling and growth, remodeling, and when needed, regeneration. Bone-forming cells, traditionally termed osteoblasts, produce, assemble, and control the mineralization of the type I collagen-enriched bone matrix while participating in the regulation of other cell processes, such as osteoclastogenesis, and metabolic activities, such as phosphate homeostasis. Osteoblasts are generated by different cohorts of skeletal stem cells that arise from different embryonic specifications, which operate in the pre-natal and/or adult skeleton under the control of multiple regulators. In this review, we briefly define the cellular identity and function of osteoblasts and discuss the main populations of osteoprogenitor cells identified to date. We also provide examples of long-known and recently recognized regulatory pathways and mechanisms involved in the specification of the osteogenic lineage, as assessed by studies on mice models and human genetic skeletal diseases.